2014
DOI: 10.1177/0022185613514206
|View full text |Cite
|
Sign up to set email alerts
|

The Australian mining industry and the ideal mining woman: Mobilizing a public business case for gender equality

Abstract: Despite ongoing ‘boom’ conditions in the Australian mining industry, women remain substantially and unevenly under-represented in the sector, as is the case in other resource-dependent countries. Building on the literature critiquing business-case rationales and strategies as a means to achieve women’s equality in the workplace, we examine the business case for employing more women as advanced by the Australian mining industry. Specifically, we apply a discourse analysis to seven substantial, publically-availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 26 publications
5
60
0
Order By: Relevance
“…Organizational sexism is similar to the construct of workplace barriers to job progression that was identified by Bailey‐Kruger () in her investigation of women miners, and it is consistent with various aspects of organizational sexism that have been identified in other prior qualitative research on women miners (Mayes & Pini, ; Murray & Peetz, ; Nowak et al, ; Pattenden, ; Tallichet, ). The organizational sexism construct also converges with the perceived burdens on women factor identified by Bergman and Hallberg () in their study of women in another male‐dominated industry.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Organizational sexism is similar to the construct of workplace barriers to job progression that was identified by Bailey‐Kruger () in her investigation of women miners, and it is consistent with various aspects of organizational sexism that have been identified in other prior qualitative research on women miners (Mayes & Pini, ; Murray & Peetz, ; Nowak et al, ; Pattenden, ; Tallichet, ). The organizational sexism construct also converges with the perceived burdens on women factor identified by Bergman and Hallberg () in their study of women in another male‐dominated industry.…”
Section: Discussionsupporting
confidence: 78%
“…Prior qualitative research has identified a series of gender‐based workplace issues for women miners (Bailey‐Kruger, ; Centre for Social Responsibility in Mining, ; Eveline & Booth, ; Lucas & Steimel, ; Mayes & Pini, ; Murray & Peetz, 2009a, 2009b, 2010; Nowak et al, ; Pattenden, ; Rolston, ; Tallichet, ; Yount, ). However, no quantitative research has investigated the empirical commonalities between these issues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the total sample size of participants, 10% were female (2) and 90% were male (18), with 65% (13) of the participants having previously worked outside of Australia in the construction industry. The gender imbalance highlighted in the above table is typical of the male-dominated construction and mining industry (Mayes and Pini, 2014). Both females in the sample size were project managers.…”
Section: Resultsmentioning
confidence: 99%